2005
DOI: 10.1097/01.ico.0000154233.56736.08
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Toxicity of Netilmicin and Ofloxacin on Intact and Mechanically Damaged Eyes of Rabbit

Abstract: Netilmicin, an antibacterial aminoglycoside, is well tolerated even in an experimental wound-healing model where the integrity of the ocular surface is compromised, whereas ofloxacin, a fluoroquinolone, appears to provoke an inflammatory response in the normal eye and a clear alteration of reepithelialization in the wounded eye. These findings suggest that netilmicin may offer a superior toxicological profile in both normal eyes and clinical situations where the integrity of the ocular epithelium is suspect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
0
18
0
5
Order By: Relevance
“…Some earlier studies compared the cytotoxicity between FQs, ofloxacin and the aminoglycoside, netilmicin. [35][36][37] They concluded that netilmicin was significantly less toxic than ofloxacin to human keratocytes, 37 to intact and mechanically damaged rabbit eyes, 36 and to rabbit corneal epithelial cells. 35 Mallari et al 38 also found an increased risk of corneal perforation after FQ treatment for bacterial keratitis, compared with treatment with fortified antibiotics (cephazolin 5% and tobramycin 1.36%).In our study, preservative-free fortified gentamicin and cefazolin were less cytotoxic to corneal epithelium cells than all the other FQ solutions tested.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies compared the cytotoxicity between FQs, ofloxacin and the aminoglycoside, netilmicin. [35][36][37] They concluded that netilmicin was significantly less toxic than ofloxacin to human keratocytes, 37 to intact and mechanically damaged rabbit eyes, 36 and to rabbit corneal epithelial cells. 35 Mallari et al 38 also found an increased risk of corneal perforation after FQ treatment for bacterial keratitis, compared with treatment with fortified antibiotics (cephazolin 5% and tobramycin 1.36%).In our study, preservative-free fortified gentamicin and cefazolin were less cytotoxic to corneal epithelium cells than all the other FQ solutions tested.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in corneal hydration are a very sensitive marker of the in vivo toxicity of various influences on the cornea [8][9][10][11][12][13]. Corneal swelling takes place due to the damage of the corneal epithelium [13,14] or endothelium [11,12,15,16], which in turns disturbs the normal corneal deturgescence mechanisms by which the cornea maintains normal hydration and hence transparency; the corneal thickness is increased, resulting in increased scatter [17].…”
Section: Discussionmentioning
confidence: 99%
“…In one such experimental system comprising monolayer cultured immortalized cell strains, strong corneal epithelial toxicity of fluoroquinolones has been shown. In addition, OFLX toxicities have been detected in experiments using rabbit cornea in vivo [8] and cultured rabbit corneal epithelial cells (SIRC) [6]. Strong toxicities to MFLX have also been detected in experiments using immortalized cultured human corneal epithelial cells (HCE) [7,9].…”
Section: Introductionmentioning
confidence: 96%